LKPD Digital Berbasis HOTS sebagai Inovasi Pembelajaran Pendidikan Pancasila untuk Meningkatkan Motivasi dan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Juwita Tindaon; Rizki Maulida; Eti Muliani (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study aims to determine the effectiveness of Higher Order Thinking Skills (HOTS)-based digital worksheets on students’ learning motivation and critical thinking skills in Civic Education (PKn) subjects at SD Negeri 040444 Kabanjahe. This study employed a quantitative approach with a quasi-experimental design using the Nonequivalent Control Group Design. The population of this study consisted of all fifth-grade students of SD Negeri 040444 Kabanjahe in the 2026/2027 academic year. The research sample consisted of two classes, namely class V-A as the experimental class and class V-B as the control class, with 25 students in each class. The data collection techniques used were observation, questionnaires, tests, and documentation. The research instruments included a learning motivation questionnaire and HOTS-based essay questions to measure students’ critical thinking skills. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, Independent Sample t-tests, N-Gain tests, and MANOVA tests. The results showed that the use of HOTS-based digital worksheets effectively improved students’ learning motivation.